Closed Loop Control of Laser Beam Welding - Otto, Andreas; Hohenstein, Ralph; Dietrich, Simon (Proceedings of the XIV. International Symposium on Gas Flow and Chemical Lasers & High Power Laser Conference, 2007)
A closed loop control for the laser beam welding process requires the collection of process parameters relevant for the machining result by means of suitable sensors, the identification of the control path as well as the feedback of the acquired data via a control algorithm and suitable actors into the process. The present paper describes such a control with the sensors respectively actors used and shows first results of controlled laser beam welding.
LFT Import::2019-08-05 (1386)
Keywords: Actors; Closed loop control; Laser beam welding; Laser material processing; Quality control; Sensors